Serum Biochemical Profile Of Malnad Gidda Breed Of Cattle In Karnataka - Sripad, K.; Kowalli, Srikant; Metri , Raju (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Blood samples were collected from 82 apparently healthy Malnad Gidda breed of animals from different geographical locations, subjected to biochemical analysis and results were analyzed. The means of SGOT, SGPT, BUN, CRE, P, Ca, ALP, Glu and T.Pro of all the 82 animals were 94.45 IU/L, 36.42 IU/L, 12.40 mg/dl, 0.92 mg/dl, 12.86 mg/dl, 11.36 mg/dl, 117.30 IU/L, 29.92 mg/dl and 9.53 percent respectively.
Keywords: Blood; Biochemical profile; Malnad Gidda breed; Karnataka